Reaction of Poplar Germplasm to Cladosporium Leaf Spot - Sharma, R. C.; Sharma, Sanjeev (Indian Forester, 2001)
Populus ciliata, an indigenous species is widely distributed in Western Himalayas and is attacked by large number of pathogens. Cladosporium humile, the incitant of leaf spot causes defoliation of great magnitude to Ciliata in nurseries and plantations. During 1997-98, an defoliation of great magnitude to Ciliata in nurseries and plantations. During 1997-98, an experiment was conducted to assess 42 clones/species/hybrids of Populus species against C. humile. Out of 24 clones of P. ciliata, none was found disease free. Eight clones were rated as susceptible while rest were highly susceptible. All other 18 hybrids/clones of P. deltoides, P. robusta, P. yunnanensis, P. trichocarpa, P. eugenii, P. oxford, P. gwayder and P. regenerata were found to be immune.